IMPLEMENTASI MEDIA PUZZLE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA MATA PELAJARAN IPA PADA MATERI SISTEM TATA SURYA DI SANGGAR BIMBINGAN MUHAMMADIYAH KEPONG MALAYSIA - Ritonga, Maulyda Syita; Saragih, Mandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether the use of puzzle media can improve students' critical thinking skills in science learning. The method used in this study is Classroom Action Research (CAR). Data collection techniques in the study were observation sheets and tests. The subjects in this study were 15 fourth grade students. The results of the study showed that the use of puzzle media in science learning can improve students' critical thinking skills from pre-cycle 50.66%, cycle I 60.66% and cycle II to 81.33%, which means that there is an increase from pre-cycle to cycle I by 10%, while the increase in cycle I to cycle II is 20%. Based on the phenomena that occur, the use of puzzle media in science learning in grade IV becomes more fun and interesting, and student participation increases in the learning process, students who become super active, increase student creativity and increase innovation and improve students' critical thinking skills.